Patent Perspectives for Corticosteroids Based Ophthalmic Therapeutics - K. Suresh, Preeti; K. Sah, Abhishek (Recent Patents on Drug Delivery & Formulation, 2014)
Eye inflammation, if untreated at right time poses the risk of vision loss. Several categories of drugs are available in the global market, but corticosteroids are still used for the treatment of ocular inflammation including anterior/ posterior uveitis, age related macular degeneration (AMD) and post cataract surgery inflammation. Although corticosteroids have well-documented side effects as compared to non steroidal anti-inflammatory drugs (NSAIDs), but they are still regarded as better anti-inflammatory agents for treating ocular inflammations. The prime concern with conventional formulations such as (ophthalmic solutions, suspensions, ointments) is low drug bioavailability due to precorneal barrier of the eye, tear turnover and rapid drainage of drug via nasolacrimal drainage and drug induced systemic toxicity. To overcome these limitations, various novel formulations of corticosteroids have been explored. These include nanoparticles, solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLC), nanomicelles, in-situ gels, iontophoresis, liposomes, nanoemulsions, microemulsions and ocular implants for the effective ophthalmic delivery of the corticosteroids. Topical nanocarriers have also been demonstrated to be promising vectors with potential application in the ophthalmic therapeutics. This review summarizes the clinical findings and patents on various corticosteroids as ocular pharmacotherapeutics.
Keywords: eye